First fired, first hired? Business cycles and immigrant labor market transitions - Huanan Xu (IZA Journal of Development and Migration, 2018)
Using individual-level Current Population Survey (CPS) data matched across adjacent months from 1996 to 2013, this paper examines immigrant-native differentials in labor market transitions to changes in the business cycle. The paper captures economic fluctuations by measuring deviations in local demand from national economic circumstances and examines monthly transitions among employment, unemployment, and nonparticipation. Immigrants are found to be first fired and first hired over the business cycle, and the aggregate unemployment gap is caused by immigrants' higher rates in the unemployment entry flow. Although to some extent the gap can be explained by variation in the immigrant-native's exposure to cycles across industry and occupation, the first fired and first hired pattern still holds. Tests for heterogeneity show that low-skilled immigrants are more vulnerable to the business cycle. Tests of the structural changes from the 2007-2009 Great Recession show that since its start, there was a secular shift in the transition probabilities that would affect all workers negatively, but cyclical volatility was mitigated for immigrants in the post-Great Recession period.
Keywords: J15; J21; J23; J61; J63; J64; 330; Labor market transitions; Labor force dynamics; Unemployment; Business cycle; Immigrant workers